The problems of consideration of cases with participation the organs of the State Tax Administration in a context of the renewed legislation on bankruptcy - Євсікова, Олена Віталіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
In the article the characteristic peculiarities of judicial consideration of cases on legal recognition of bankrupt adjudged with participation the organs of the State Tax Administration of Ukraine, the analysis of changes to the Law of Ukraine «About the renewal of solvency of debtor or legal recognition his of bankrupt adjudged », the positive and negative consequences of such changes are opened